Decomposing firm value - Belo, Frederico; Gala, Vito D.; Salomao, Juliana; Vitorino, Maria Ana (Journal of Financial Economics, 2022)
What are the economic determinants of a firm’s market value? We answer this question through the lens of a generalized neoclassical model of investment with quasi-fixed labor and three heterogeneous capital inputs. We estimate the structural model using firm-level data on US firms and find that, on average and depending on the industry, installed labor force accounts for 14–21% of firms’ market value, physical capital accounts for 30–40%, knowledge capital accounts for 20–43%, and brand capital accounts for 6–25%. Our analysis provides direct empirical evidence for the importance of labor and intangible capital inputs for understanding firm value.